A 'history of problematizations' for dementia education: a Foucauldian approach to understanding the framing of dementia. (June 2019) - Knifton, Chris; Yates, Scott
Background: Debates relevant to both undergraduate and postgraduate nurse education regarding the conceptualisation and disciplinary ownership of dementia, including its framing as a neuro-psychiatric condition, a terminal illness or a consequence of ageing, are important in supporting an understanding of the lived experience of dementia for individuals and their family carers and how, as a condition, it has come to be problematised in Western society. The work of Michel Foucault is useful in setting this debate within a critical historical context. Aims: Using Foucault's 'history of problematizations' we present such debates around dementia's conceptualisation in Western society and consider how a Foucauldian critical historical project influences nursing education by re-examining the problematisation of dementia within society, what it is to be a person with dementia, and how alternative conceptualisations shape how we see the condition – as well as how we provide learning opportunities for dementia-care professionals. Results: Six differing ways of conceptualising or problematising dementia were found (as a natural consequence of ageing, a mental disorder, a bio-medical disease, a neuro-cognitive disorder, a disability and a terminal illness), each offering alternative ways we might present it in an educational context. Conclusions: We argue for both undergraduate and postgraduate student nurses to engage in learning that locates what it is to be a person with dementia within particular conceptual frameworks that would allow understanding of how these ideas or constructs are reliant on historically contingent assumptions. Here, taken-for-granted assumptions are unsettled, and a more critically reflective position is adopted. This will have an impact on the type of nurse to emerge from educational institutions, thus also affecting service delivery and the dementia care provided, as well as the knock-on effects for dementia education in other medical, health and social care courses and for institutions whose role it is to approve professional practice curricula content.